Association between parental height and short stature of children aged 7 to 11 years in Kulon Progo, Yogyakarta - Shafira Khalisa Hanun; Janatin Hastuti; Mei Neni Sitaresmi; Madarina Julia (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2026)
Background: Stunting remains a concern worldwide. The prevalence of stunting in Indonesia remains high, and Kulon Progo has the fifth-highest stunting prevalence in Yogyakarta Province. Objective: This study aimed to determine the associations between parental height and the short stature of children aged 7-11 years in Kulon Progo Regency. Methods: This study was conducted on 62 children as cases (23 boys, 39 girls) and 62 children as controls (23 boys, 39 girls), aged 7-11 years. Cases were defined as children with short stature (< -2 SD) based on height-for-age Z-score (HAZ), and normal children (≥ -2 SD HAZ) were used as controls. Height of children and both parents was measured. Mid-parental height (MPH) was calculated. Health history was observed. The data were analyzed using Chi-Square, Fisher's test, and simple linear regression. Results: Short children had an average height of 118.33 (±4.69) in boys and 119.98 (±4.39) in girls. Normal children had an average height of 127.81 (±5.48) in boys and 131.13 (±6.67) in girls. Short stature children were significantly associated with paternal height (OR=2.88; p=0.004), maternal height (OR=2.88; p=0.004), boys’ MPH (OR=10.37; p=0.001), and girls’ MPH (OR=2.91; p=0.022). Boys’ HAZ was correlated with father’s HAZ (r=0.40; p=0.006), mother’s HAZ (r=0.51; p≤0.001), and MPH HAZ (r=0.63; p≤0.001). Girls’ HAZ was correlated with father’s HAZ (r=0.37; p=0.001), mother’s HAZ (r=0.32; p=0.004), and MPH HAZ (r=0.45; p≤0.001). There was no significant association between short stature and the mother's gestational age, anemia, and chronic energy failure, as well as the child's history of low birth weight, infection, and exclusive breastfeeding. Conclusions: Short-stature children were associated with paternal and maternal height and MPH, but not with mothers’ or children’s health history.